PP.12.09: NEURAL BIOLOGY OF PURE AUTONOMIC FAILURE. (June 2015) - Guo, L.; Esler, M.; Lambert, E.; Phillips, S.; Corcoran, S.
Abstract : Objective: Patients with autonomic insufficiency syndromes accompanied by postural hypotension are commonly referred to hypertension experts, who are often expected to be skilled in low BP disorders also. One phenotype, pure autonomic failure (PAF), remains enigmatic. PAF is usually attributed to isolated degeneration of postganglionic sympathetic nerves, without CNS disease, as is conveyed in the name. Our results reported here suggest otherwise. Design and method: Nine patients with PAF and a reference group of 9 older healthy people aged 50–80 years were studied using novel molecular methods for studying sympathetic nerve proteins. As expected, the PAF patients had intractable postural hypotension without CNS disease, with diagnosis confirmed by presence of markedly reduced release of noradrenaline from sympathetic nerves, measured by isotope dilution (total noradrenaline spillover < 150 ng/min compared with 300–900 ng/min in health) and near-absence of sympathetic nerve firing recorded with microneurography. Results: When we tested for anticipated absence of specific sympathetic nerve proteins in biopsied subcutaneous forearm vein samples in PAF patients, veins being a rich source of sympathetic nerves, unexpectedly we found normal abundance of the noradrenaline transporter, NET and the vesicular transporter, VMAT2 (figure), unequivocal evidence that sympathetic nerves were present. Figure. No caption available. Western blot analysis of sympathetic nerve proteins, accessed by forearm vein biopsy. The abundance of NET and VMAT2 was not reduced in PAF (P > 0.1 compared with normals). GAPDH served as a marker protein for protein loading of the gel. Conclusions: These results suggest that the abnormality in PAF, rather than being neurodegenerative, may be a sympathetic nerve membrane fault causing electrical silence so that, as we find here, microneurography registers no sympathetic nerve firing, electro-coupled noradrenaline release is nearly absent and neural postural circulatory homeostasis is severely compromised. The fault may be epigenetic, as PAF has onset in later life.